Apprentice pay in Britain, Germany and Switzerland : institutions, market forces, market power - Ryan, Paul [Verfasser]; Backes-Gellner, Uschi [Verfasser]; Teuber, Silvia [Verfasser]; Wagner, Karin [Verfasser] (My University, 2012)
"Although trainee pay is central to the economics of work-based training, institutionalists have paid it little attention, while economists typically assume that it is set by market clearing. We document large differences in the pay of metalworking apprentices in three countries: relative to the pay of skilled employees, it is high in Britain, middling in Germany, and low in Switzerland. Combining fieldwork evidence with national survey data, we associate apprentice pay with both institutional attributes and market forces: specifically, with trade union presence and goals, employer organisation, the contractual status of apprentices, the supply of eligible and interested young people, and public subsidies. Apprentice pay appears to have fallen in Britain and Germany as bargaining coverage has declined." (Authors' abstract, BIBB-Doku)
Keywords: S 2.1.6 Arbeits- & Tarifrecht; S 4.2.1 Personalkosten; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); I 2.2.1 Westeuropa; I 2.1 Deutschland; Ausbildungsvergütung; Einkommensstruktur; Metallberuf; Internationaler Vergleich; Großbritannien; Bundesrepublik Deutschland; Schweiz